Reading Comprehension on Smartphones, A Comparison with Computers - Cotton, Andrés; Benedetti, Pedro; Abusamra, Valeria (Cuadernos de Lingüística Hispánica, 2023)
This study aims to compare the effects of smartphones and computers on reading comprehension of both narrative and expository texts among adults of different ages and educational levels. To do so, a reading task followed by multiple-choice questions was designed, and 2391 volunteers participated; their educational levels, ages, and reading devices were recorded. Of these, 1510 worked with narrative text and 881 with expository text. Our analyses included descriptive statistics, Mann-Whitney U, Kruskal-Wallis tests, and simple and multiple regressions. Results indicate that while smartphones yield disadvantages with expository texts —especially among younger groups, from whom better performance on smartphones is generally expected— such disadvantages are not observed with narrative texts. Furthermore, educational level showed a significant effect under all reading conditions. In line with existing research, our results reveal a significant disadvantage associated with reading expository texts on smartphones; accordingly, we recommend employing alternative reading media whenever feasible.